Analyzing Krazy Kode. - Neville-Neil, George V. (Communications of the ACM, 2025)
This piece explores the personal and emotional dimensions of reading and writing code, suggesting that programming style often reflects the coder's mental and emotional state. Despite standardized coding practices, code remains as diverse and psychologically revealing as its authors—sometimes playful, sometimes angry, and at times bewilderingly chaotic. By tuning into these emotional cues, readers can gain insight into both the functionality and the mindset behind the code, reinforcing the idea that programming is as much about human communication as it is about logic.